Minimal hermitian matrices with fixed entries outside the diagonal - Andruchow, Esteban (2008)
We survey some results concerning the problem of finding the complex hermitian matrix or matrices of least supremum norm with variable diagonal. Some qualitative general results are given and more specific descriptions are shown for the 3 x 3 case. We also comment some results and examples concerning this approximation problem.